A review of machine learning in scanpath analysis for passive gaze-based interaction - Mohamed Selim, Abdulrahman; Barz, Michael; Bhatti, Omair Shahzad; Alam, Hasan Md Tusfiqur; Sonntag, Daniel (Frontiers in Artificial Intelligence, 2024)
The scanpath is an important concept in eye tracking. It refers to a person's eye movements over a period of time, commonly represented as a series of alternating fixations and saccades.Machine learning has been increasingly used for the automatic interpretation of scanpaths over the past few years, particularly in research on passive gaze-based interaction, i.e., interfaces that implicitly observe and interpret human eye movements, with the goal of improving the interaction. This literature review focuses on research on machine learning applications in scanpath analysis for passive gaze-based interaction between 2012 and 2022, including a total of 77 publications.We provide insights on research domains and common learning tasks in passive gaze-based interaction and present common machine learning practices from data collection and preparation to model selection and evaluation. We discuss commonly followed practices and identify gaps and challenges, especially concerning emerging machine learning topics, to guide future research in the field.